Determinants of Mobile Broadband Use in Developing Economies: Evidence from Sub-Saharan Africa - Maude Hasbi; Antoine Dubus (International Telecommunications Society (ITS), 2019)
Broadband is seen as a vector of economic growth and social development. In the developing world, mobile technologies are widely adopted and mobile broadband is progressively rolled-out with high expectations on its impact on the countries' development. We highlight what the determinants of mobile broadband use are in four Sub-Saharan countries. Using micro-level data coming from household surveys over 5 years, from 2013 to 2017, we show that the ownership of a mobile phone is highly correlated with mobile broadband use. We also show that for non-mobile owners, the ownership of an active SIM card is a prerequisite for using mobile broadband. In addition, mobile money users tend to be more likely to use mobile broadband. This could highlight the existence of a learning effect. By using mobile money services, individuals gain more experience and are more inclined to use more advanced technologies, such as mobile broadband. Although we show that mobile broadband use is increasingly growing, a large part of the population, mainly composed of poor households living in rural areas, is still left behind. This raises concerns on the increase of the digital gap between people and territories.
Keywords: I30; O12; L50; L96; O55; 330; Mobile Broadband Use; Developing Economy; Economic Growth; Inequality; Digital Gap